Solat tracking system - Nur Khuzairy, Jamaludin (2008)
As we can see now, the earth become hot because of the global warming. Why this thing happen. Many things happen that can cause pollution. For examples here, why we use gas to generate energy while we can use sunlight to generate energy. So, the project that wants to develop here is called “Solar Tracking System”. Solar tracking system is the project that used PIC16F877A microcontroller as a brain to control the whole system. The LDR (Light Dependant Resistor) had been used to sense the intensity of light at 30 degree each or 180 degree total and sent the data to the microcontroller. This microcontroller will compare the data and rotate a stepper motor to the right direction. The stepper motor will rotate the solar panel based on the highest intensity of light. This project had been proved effectively to generate high energy in only one rotational solar panel.